The Czech labour market: Adaptation of young people to the advent of Industry 4.0 - Zuzana Dohnalová; Kamil Dobeš; Jan Kramoliš (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2021)
The focus of the paper was to conduct an analysis of the selected qualitative and quantitative aspects of the labour market and the potential ability of the young generation to adapt to the new conditions of their prospective employment. The primary data were obtained in the form of a questionnaire survey. The total of 2,817 respondents were contacted via email containing a research hyperlink. The respondents were secondary school students studying in the Czech Republic. The obtained data were collected in Excel and further processed by statistical methods, the Pearson test using χ quadrate. The option of choosing several occupations was evaluated by means of the so-called professional specialisation index. Secondary data were used to determine the development of trends on the Czech labour market in the current conditions of the Industry 4.0 onset. The respondents most often chose occupations in the fields of technology, industry and construction out of the eleven occupational areas offered. More than a quarter of respondents chose their preferred profession in this area. This is a positive finding in terms of the focus of the economy on Industry 4.0.
Keywords: J21; J24; L0; E24; 330; Czech Republic; Microeconomics; Labour Market; Industry 4.0; Job; Occupation